Drivers of poverty reduction in lagging regions: Evidence from rural Western China - Luc Christiaensen; Lei Pan; Sangui Wang (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
Using 2000-04 panel data this study analyses the pathways rural households followed out of poverty in two lagging provinces of China, Inner Mongolia and Gansu. Rising labour productivity in agriculture has been key, and still holds much promise. Labour mobility has also been important in Gansu. So far, rural diversification has not proven to contribute much to poverty reduction. Income transfers and agricultural tax abolishment have helped at the margin. Overall, the findings highlight that the scope for reducing poverty in lagging rural regions is often substantial in agriculture, also in countries where non-agriculture drives overall growth.
Keywords: I32; J61; O12; O13; R23; 330; agriculture; migration; rural nonfarm employment; lagging region; poverty